Pengaruh Podcast dan YouTube Tafsir Al-Quran terhadap Literasi Digital Santri - Salsa Fadilah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This research aims to examine the influence of podcasts and YouTube videos featuring Qur’anic interpretation on the digital literacy skills of Islamic boarding school students. The study uses a descriptive quantitative method, with information gathered through observations and questionnaires. The participants involved were students from an Islamic boarding school environment. The findings reveal that digital media platforms, particularly podcasts and YouTube, play an important role in enhancing students’ digital literacy, especially in accessing, assessing, and critically interpreting religious materials. Furthermore, combining religious learning with digital technology increases students’ enthusiasm, involvement, and participation during the learning process. These media platforms also motivate students to become more independent and proactive in deepening their understanding of Islamic studies. Overall, digital media can function as an effective medium for supporting religious education as well as strengthening digital literacy skills. Therefore, educators are encouraged to assist students in identifying trustworthy, authentic, and reliable information sources in order to prevent misinformation and create more meaningful learning experiences.